From Violence to Veneration: The Life of Guelph’s Samuel Venerable - DeLaurentis, Elysia (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
Having grown up enslaved in northern Kentucky, Samuel Venerable fled to Ontario in the early nineteenth century, establishing himself in Toronto, then London, before moving to Guelph where he lived out his last thirty years. He faced the same hardships as other refugees to Ontario, yet in many ways he was exceptional. He overcame odds not only to survive, but to live a productive and remarkably long life, and he rose from the lowliest social strata to become a man revered. Despite being illiterate, Venerable left a valuable record for historians. By relying on information recorded during his lifetime, and at the time of his death, this article focusses on Samuel Venerable and those with whom he formed connections to offer a fuller understanding of the successes and struggles faced by some Black Ontarians in the nineteenth century.